Development and Testing of a Method for Detecting Lujo Virus RNA by Reverse Transcription and Real Time Polymerase Chain Reaction - E. V. Naidenova; V. G. Dedkov; D. A. Agafonov; A. M. Senichkina; M. V. Safonova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2021)
The aim of the study was to develop and assess the efficacy of a method for Lujo virus RNA detection in clinical and biological samples using one-step real-time RT-PCR.Materials and methods. In order to select the conservative regions of the genome, we utilized the available in GenBank database Lujo virus sequences (https://www.ncbi. nlm.nih.gov/genbank) aligned in BioEdit 7.2.5 software package ( (IbisBiosciences, USA). To conduct one-round RTPCR, reverse transcriptase and TaqF-polimerase were used. Recombinant Escherichia coli strain, XL1-Blue, containing pGEM-T plasmid with inserted synthetically-generated fragment of the virus genome, was produced to make positive control sample (PCS). Constructed recombinant plasmids were used for creating RNA-containing PCS with protective protein shell of MS2-phage. Determination of specificity of the developed method was performed with the help of control panel of RNA and DNA of 23 viral strains related to 10 families; the sensitivity – the panel of biological samples artificially contaminated with PCS. Further testing was carried out at the premises of laboratory of the Russian-Guinean Center for Epidemiology and Prevention of Infectious Diseases (Kindia, Republic of Guinea) on 265 blood sera from practically healthy persons, 110 blood sera of cattle, 83 suspensions of ticks, and 165 suspensions of organs of small mammals collected in the territory of Guinea.Results and discussion. Two conservative polymerase gene fragments have been chosen as targets for Lujo virus RNA detection using RT-PCR. The combination of primers and probes has been experimentally selected, optimum composition of reaction mixture for PCR and mode of RT-PCR set-up established, as well as control samples C+, internal control, positive control sample developed. Sensitivity of the proposed method is 5·103  GE /ml, specificity – 100 %.